Knowledge, attitude and practice regarding healthy diet and physical activity among overweight or obese children - Abdul Manaf, Rosliza; Ismail, Suriani; Mohd Zulkefli, Nor Afiah (IJPHCS, 2018)
Background: Inculcating healthy life style such as the habit of consuming balanced diet and performing physical activity among children could prevent them from becoming overweight or obese and thus avoid the risk of chronic diseases related with obesity. Such efforts are challenging yet crucial. This study assessed the immediate effect on children's knowledge, attitude and practices regarding healthy diet and physical activity following an awareness programme. Materials and Methods: A half-day childhood obesity awareness programme was conducted to encourage the practise of healthy diet and physical activity, and persuade against unhealthy food consumption and sedentary life style. The programme was carried out among 30 children aged 8-11year old in an international school in Putrajaya who were overweight or obese. A pre-and post-test design was carried out to evaluate their knowledge, attitude, and practice toward healthy diet and physical activity using pretested questionnaire. Comparison of pre-and post-test' scores were carried out using paired t test. Result: Over half of the respondents were female (63.3%) and obese (70.0%). The mean(sd) knowledge and attitude scores for healthy diet were 2.00(0.91) and 2.33(0.84). The mean knowledge score for physical activity was better i.e., 3.10(1.32) but the attitude scores was very low 0.87(1.07). After the programme, although not statistically significant there were slight increases in all scores, except 'intend to practise' physical activity after the programme. Conclusion: The knowledge, attitude and practices regarding healthy diet and physical exercise among these children were low. A series of improved and validated programmes are recommended for greater impact.